1996
DOI: 10.1128/jvi.70.12.8872-8878.1996
|View full text |Cite
|
Sign up to set email alerts
|

A hypervariable region in VP1 of chicken infectious anemia virus mediates rate of spread and cell tropism in tissue culture

Abstract: Chicken infectious anemia virus (CIAV) is a unique infectious agent with an amino acid composition that has been found to be remarkably conserved even in isolates from different parts of the world. We have characterized field isolates of CIAV which vary significantly in terms of their abilities to replicate in culture, demonstrating a biological difference between isolates. Two sublines of MDCC-MSB1 cells that differ in their abilities to support CIAV were identified. In the MSB1(S) subline the CIA-1 isolate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 24 publications
1
72
0
4
Order By: Relevance
“…Although IBDV had been isolated and characterized from the same sample (Islam et al, 2001), repeated attempts to isolate BD‐3 CAV in MDCC‐MSB1 cells were not successful. Field isolates of CAV can vary significantly in their ability to replicate in MDCC‐MSB1 cells and different sublines of MDCC‐MSB1 cells also may vary in their susceptibility to CAV (Renshaw et al, 1996; Calnek et al, 2000). BD‐3 CAV could be one of those strains which do not grow in the MDCC‐MSB1 cell line used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although IBDV had been isolated and characterized from the same sample (Islam et al, 2001), repeated attempts to isolate BD‐3 CAV in MDCC‐MSB1 cells were not successful. Field isolates of CAV can vary significantly in their ability to replicate in MDCC‐MSB1 cells and different sublines of MDCC‐MSB1 cells also may vary in their susceptibility to CAV (Renshaw et al, 1996; Calnek et al, 2000). BD‐3 CAV could be one of those strains which do not grow in the MDCC‐MSB1 cell line used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…VP3 is an apoptosis inducing protein (Noteborn et al, 1994). On the basis of comparison between Cux‐1 and CIA‐1, Renshaw et al (1996) suggested that an amino acid substitution at position 118 of the VP3 could influence nuclear localization of the protein and the development of distinct apoptotic bodies in cell culture. However, our alignment revealed that R at position 118 is present only in Cux‐1 (N), but Cux‐1 (M) and all other CAV strains, including BD‐3 CAV, have C at this position (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of predicted amino acid sequences, minor differences have been noted particularly in the VP1 amino acid sites 139-151. The observed differences in the hypervariable region had impact on the predicted protein structure of VP1 [48][49][50]. In this study, the phylogenetic analysis of VP1 embodied the diversity of CAV, while the VP2 and VP3 embodied the conservatism.…”
Section: Discussionmentioning
confidence: 70%